2004
DOI: 10.1086/378578
|View full text |Cite
|
Sign up to set email alerts
|

The Size Evolution of High-Redshift Galaxies

Abstract: Hubble Space Telescope images of high-redshift galaxies selected via color and photometric redshifts are used to examine the size and axial ratio distribution of galaxies as a function of redshift at look-back times Gyr. t 1 8 These parameters are measured at rest-frame UV wavelengths (1200 ! l ! 2000 ) on images with a rest-Å A frame resolution of less than 0.8 kpc. Galaxy radii are found to scale with redshift approximately as the Hubble parameter . This is in accord with the theoretical expectation that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
433
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(506 citation statements)
references
References 31 publications
65
433
8
Order By: Relevance
“…The half light radius of these LAEs at z = 2, however, is not correlated to the EW in Lyman-α. The stellar massradius relation evolves in redshift as (1 + z) −1 , in a manner consistent with the size evolution found by Bouwens et al (2004) and Ferguson et al (2004) for LBGs at z ≥ 2-5 and by Hathi et al (2008) at z ∼ 5-6.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The half light radius of these LAEs at z = 2, however, is not correlated to the EW in Lyman-α. The stellar massradius relation evolves in redshift as (1 + z) −1 , in a manner consistent with the size evolution found by Bouwens et al (2004) and Ferguson et al (2004) for LBGs at z ≥ 2-5 and by Hathi et al (2008) at z ∼ 5-6.…”
Section: Introductionsupporting
confidence: 87%
“…A more reliable distribution for the axial ratio parameter b/a, following Ferguson et al (2004) can be adopted in our simulations, but we must stress that, in their work, this functional form is measured on a sample of photometrically selected candidate galaxies at z ∼ 4, and it is not clear whether this should be applied also to our z ∼ 7 sample. A more detailed approach, like that adopted in Law et al (2012) work, is more appropriate but very complex and goes beyond the aims of this paper.…”
Section: Is This Picture Conclusive?mentioning
confidence: 99%
“…Taking the BB paradigm for granted, Ferguson et al (2004) found the galaxy radii to scale with redshift approximately as the Hubble parameter H -1 (z), i.e., approximately ~ (1 + z) -1 . They say that "This is in accord with the theoretical expectation that the typical sizes of the luminous parts of galaxies should track the expected evolution in the virial radius of dark matter halos."…”
Section: Angular Sizementioning
confidence: 99%
“…For the U-dropout galaxies, we have used the effective volume derived by Steidel et al (1999). For the B-dropout galaxies, we have simulated artificial LBGs in the GOODS data with a distribution of colors and sizes that match the observed B-dropout properties (see Ferguson et al 2004). We then measure photometry for the simulated galaxies and apply our color selection criteria to derive the probability that a LBG with given magnitude and redshift is detected in the data, .…”
Section: The Integrated Seds Of High-redshift Galaxiesmentioning
confidence: 99%